Minimizing the risk to human health due to the ingestion of arsenic and toxic metals in vegetables by the application of biochar, farmyard manure and peat moss. (15th May 2018) - Nawab, Javed; Ghani, Junaid; Khan, Sardar; Xiaoping, Wang
Abstract: Mining activity releases toxic metals (TMs) into the soil ecosystem and creates serious problems for the environment and human beings due to their adverse eco-toxilogical impacts. Currently, several remediation techniques can be used to immobilize TMs within contaminated soil. The present study focuses on the application of different organic amendments biochar (B), farmyard manure (FYM) and peat moss (PTM) – at different application rates (1%, 2% and 5%) in mining-impacted agricultural soil to immobilize TMs (Ni, Cr, As, Zn, Cd and Pb) and minimize their bioaccumulation in pea ( Pisum sativum ) and chili ( Capsicum annuum ) and the associated human health risk. Among the organic amendments, the treatments at the 5% application rate of B, FYM and PTM significantly ( p  ≤ 0.001) reduced the bioavailability of TM concentrations in amended soil and increased pea and chili plants' and fruits' biomasses when compared with the control. Moreover, risk assessments showed that B, FYM and PTM decreased the daily intake and health risk associated with the consumption of vegetables effectively for individual TMs compared with the control. The highest application rate of 5% significantly ( p  ≤ 0.001) reduced the average daily intake of TMs and their health risk, as compared to 1% and 2%, for both adults and children. The health risk index (HRI ˂ 1) values were lower (and within safety limits) for adults and children consuming vegetables grown on organic-amended soils. The results indicate that the B5% treatment of this mining-impacted agricultural soil was the most efficient at increasing plant and fruit biomasses and reducing the bioavailability, bioaccumulation and daily intake of TMs and their potential health risk through consumption of vegetables such as pea and chili, as compared to FYM, PTM and the control treatment. Graphical abstract: Image 1 Highlights: Mining activity contaminates agricultural soil with toxic metals (TMs) in impacted areas. Biochar (B), farmyard manure (FYM) and peat moss (PTM) immobilize TMs within the soil ecosystem. B5%, FYM5% and PTM5% restrict the entry of TMs into the food chain by reducing their bioavailability. B5% is the most efficient at decreasing the bioavailability, uptake, daily intake and health risk of TMs in vegetables.